Effect of annealing temperature of sol-gel TiO2 buffer layer on microstructure and electrical properties of Ba0.6Sr0.4TiO3 films - Ibrahim, N.B; Yusrianto, E; Zalita, Z; Ibarahim, Z (Universiti Kebangsaan Malaysia, 2012)
Ba0.6Sr0.4TiO3 (BST) thin films were prepared on TiO2 buffer layers. The buffer layers were prepared using sol-gel method, followed by annealing process at different temperature from 300 to 55oC with 50oC interval for 30 min in air. The microstructure and electrical properties of BST were then investigated. Increasing the annealing temperature increased. The buffer layer thickness BST films prepared on thicker buffer layer showed improved crystallinity. Without the buffer layer, BST crystallization cannot occur at 700oC. However with buffer layer, 700oC is sufficient for the process to occur. The BST grain size increased with the buffer grains increment. The existence of TiO2 buffer layer increased the current density. The dielectric constant, εr´ and dielectric loss were not affected much by the buffer layer except at frequency around 1 kHz that showed an increment in the εr’ value with the increment of the annealing temperature.